Physiological and Pharmacological Effects of Glucocorticoids on the Gastrointestinal Tract - Filaretova, Ludmila; Podvigina, Tatiana; Yarushkina, Natalia (Current Pharmaceutical Design, 2020)
The review considers the data on the physiological and pharmacological effects of glucocorticoids on the gastric mucosa and focuses on the gastroprotective role of stress-produced glucocorticoids as well as on the transformation of physiological gastroprotective effects of glucocorticoids to pathological proulcerogenic consequences. The results of experimental studies on the re-evaluation of the traditional notion that stress-produced glucocorticoids are ulcerogenic led us to the opposite conclusion suggested that these hormones play an important role in the maintenance of the gastric mucosal integrity. Exogenous glucocorticoids may exert both gastroprotective and proulcerogenic effects. Initially, gastroprotective effect of dexamethasone but not corticosterone, cortisol or prednisolone can be transformed into proulcerogenic one. The most significant factor for the transformation is the prolongation of its action rather the dose. Gastrointestinal injury can be accompanied by changes in somatic pain sensitivity and glucocorticoids contribute to these changes playing a physiological and pathological role.
Keywords: Stress